Suma cervantina. Ed. de J. B. Avalle-Arce y E. C. Riley. Tamesis Books, London, 1973; xi + 452 pp. (Serie A, Monografías, 14). - Rodríguez-Luis, Julio (El Colegio de México, 1974)
Se reseñó el libro: Suma cervantina.